Effects of hydroxytyrosol dose on the redox status of exercised rats: the role of hydroxytyrosol in exercise performance - Saad Al Fazazi; Rafael A. Casuso; Jerónimo Aragón-Vela; Cristina Casals; Jesús R. Huertas (Taylor & Francis Group, 2018)
Background Hydroxytyrosol (HT) is a polyphenol found in olive oil that is known for its antioxidant effects. Here, we aimed to describe the effects of a low and high HT dose on the physical running capacity and redox state in both sedentary and exercised rats. Methods Male Wistar rats were allocated into 6 groups: sedentary (SED; n = 10); SED consuming 20 mg/kg/d HT (SED20; n = 7); SED consuming 300 mg/kg/d HT (SED300; n = 7); exercised (EXE; n = 10); EXE consuming 20 mg/kg/d HT (EXE20; n = 10) and EXE consuming 300 mg/kg/d HT (EXE300; n = 10). All the interventions lasted 10 weeks; the maximal running velocity was assessed throughout the study, whereas daily physical work was monitored during each training session. At the end of the study, the rats were sacrificed by bleeding. Hemoglobin (HGB) and hematocrit (HCT) were measured in the terminal blood sample. Moreover, plasma hydroperoxide (HPx) concentrations were quantified as markers of lipid peroxidation. Results In sedentary rats, HT induced an antioxidant effect in a dose-dependent manner without implications on running performance. However, if combined with exercise, the 300 mg/kg/d HT dosage exhibited a pro-oxidant effect in the EXE300 group compared with the EXE and EXE20 groups. The EXE20 rats showed a reduction in daily physical work and a lower maximal velocity than the EXE and EXE300 rats. The higher physical capacity exhibited by the EXE300 group was achieved despite the EXE300 rats expressing lower HGB levels and a lower HCT than the EXE20 rats. Conclusions Our results suggest that a high HT dose induces a systemic pro-oxidant effect and may prevent the loss of performance that was observed with the low HT dose.